Neolatin héber átiratok? A 17. századi héber köszöntőversek költészeti háttere és Szenci Molnár Albert héber nyelvtudása - Zsengellér, József (Studia Litteraria, 2026)
Despite the fact that Albert Molnár Szenci revised the Hungarian Bible translation on two occasions and translated the Geneva Psalms into Hungarian, there is a paucity of information about his knowledge of Hebrew. A survey of his studies and his Hebrew teachers reveals that he had the opportunity to learn the language thoroughly. Nevertheless, he did not become a writer of the 17th-century Hebrew Greeting Poems. It was previously hypothesized that these Hebrew poems were Hebrew transcriptions of poems originally written in Latin. The captions and poetic devices of these poems lend support to this hypothesis. However, a thorough examination of these poems, along with an existing bilingual poem, suggests that these carmina were originally composed in Hebrew.